Analysis Of Farmers Knowledge Attitude And Skills Influence On Soybean Crops In Maros Regency - Dewi Puspitasari (Information Technology and Science (ITScience), 2026)
This study aims to determine the level of knowledge, attitudes, and skills of farmers regarding soybean crops in Tompobulu Village, Tompobulu District, Maros Regency. The population in this study was taken using a simple random sampling method from soybean farmers. The population of soybean farmers was 217 farmers, and 15% were taken as a sample, so the sample taken was 32 soybean farmers. Data analysis used was descriptive quantitative, the data obtained and collected were then analyzed based on predetermined methods and aimed to assess the level of knowledge, attitudes, and skills of farmers. The results showed that the level of knowledge of soybean farmers was in the moderate category, the level of attitude of soybean farmers was in the moderate category, and the level of skills of soybean farmers was in the moderate category. The level of knowledge of farmers regarding soybean plants in Tompobulu Village, Tompobulu District, Maros Regency is included in the moderate category with an average score of 60.5, which means that farmers already know enough about how to farm soybean plants. Irrigation is carried out in the morning and evening without making the soil too muddy or even dry with a score of 1.75 with an average score of 58.3 obtained moderate criteria, this is because there are some farmers who only rely on rain in irrigating their soybean plants.